MENEROBOS BATAS PELINDUNGAN HUKUM BAGI SUB PENYEDIA JASA DALAM PERJANJIAN KONTRAK KONSTRUKSI DALAM KERANGKA HUKUM POSITIF - Iswandy, Wahju Iswandy; Rosalinda Elsina Latumahina (Nusantara Hasana Journal, 2025)
The research aims to analyze the legal protection for sub-service providers in construction contracts with a comprehensive approach. The focus of the research is to unravel the limitations and strengthen the rights and obligations of the parties in accordance with the positive legal framework. Sub-service providers play a role in the success of construction projects thanks to the specialized expertise they have. Ironically, their legal position is often vulnerable to uncertainty and risks that can lead to injustice. So in this study, it seeks to explore the lack of legal protection for sub-service providers in practice. In the context of the construction industry, the legal relationship between the parties requires adaptive and clear regulations. Sub-service providers not only face risks related to implementation responsibilities, but also the problem of sharing rights and contractual provisions that are often unfair. Raises fundamental questions about the effectiveness of legal protection and the fair implementation of obligations between the parties to a construction contract. The research method was used by making a normative juridical analysis used to evaluate various applicable laws and regulations related to construction contracts, especially regarding provisions for sub-service providers. The research discusses positive law enforcement practices and potential obstacles during contract implementation with the aim of obtaining an overview of legal protection when contracts are properly executed. The results of the study show that even though there are regulations regulating construction contract agreements according to specific provisions and protection for the position of sub-service providers, it is still very limited. In the legal relationship, the condition is actually more favorable to the service provider as a contractor, and the rights of sub-service providers are often ignored by both parties because disputes can arise. Developments in construction services require regulatory updates to address complex challenges in industries that involve multiple parties. To maintain a balance of interests between various actors in the construction sector, especially for sub-service providers who are often in vulnerable positions, it is necessary to strengthen legal protection with an emphasis on rights, obligations, and the application of clear sanctions. This research uses a comprehensive approach to a positive legal framework in the hope of recommending significant changes in regulations and policies to be more inclusive and responsive to the existence of sub-service providers.